Chemical Weapons in the Iran-Iraq War (1980–1988) 3. Medical Consequences of Chemical Warfare - M. V. Supotnitskiy; N. I. Shilo; V. A. Kovtun (Вестник войск РХБ защиты, 2023)
The third article in the series is dedicated to the medical consequences of the chemical warfare between Iran and Iraq during the war (1980–1988). The UN official documents and materials, declassified CIA documents, as well as other open Western and Iranian sources have been used during its preparation. The chemical war against the Islamic Republic of Iran was waged in the conditions of the increased power of chemical weapons, when the Iraqi army had the opportunity to carry out multiple massive chemical aviation strikes at operational depth and to use multiple launch rocket systems for the massive use of toxic substances in the tactical zone. The mortality from sulfur mustard reached 30 % in some sections of the front, that was impossible during the First World War. The unpreparedness of the Iranian army to chemical warfare led to the serious irretrievable losses among the Iranian military during the war (25 thousand people) and to the grave long-term consequences for the health of the survivors (at least 100 thousand people), despite of the relatively small amount of poisonous substances used by Iraq (2.54 thousand tons). As in World War I, sulfur mustard turned out to be the «king of gases» in this war. The Iranian scientists find out that even after the curing of acute lesions in hospitals the pathological process caused by the action of poisonous substances does not stop. It enters the phase of delayed effects, manifested with the age of the patient. There are the irreversible obstructive processes in the lungs («mustard lung»). In 2014 about 45 thousand Iranians suffered from late respiratory complications caused by sulfur mustard. There are the eczemoid dermatitis, vitiligo, psoriasis and discoid lupus erythematosus. There are the delayed ulcerative keratitis and various lesions in the neurological tissues of the eye and in the ocular fundus of the vascular system. There are other pathologies as well. The article contains a large number of photographs, diagrams and images, never published in Russian medical literature before.